Northern blotting of endogenous full-length human-specific LINE-1 RNA - Maisa I Alkailani (21842354) (2024)
LINE-1 belongs to a family of DNA elements that move to new locations in the genome in a process called “retrotransposition.” This is achieved by a copy-and-paste mechanism with the aid of an RNA intermediate. The full-length LINE-1 is responsible for most retrotransposition activity in the human genome. Detecting the active LINE-1 RNA at the endogenous level is challenging due to its small percentage among inactive copies and its different forms of transcripts. Here, we describe a method of designing RNA probes to detect active LINE-1 by northern blotting and use optimized conditions and tools to make the detection practical. This method uses a classical long RNA probe and provides an alternative way to detect LINE-1 RNA using multiple short RNA probes. Other Information Published in: Biology Methods and Protocols License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/biomethods/bpae036